1982
DOI: 10.1093/ptj/62.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tone-Inhibiting Casts and Orthoses on Gait

Abstract: In the adult case presented, inhibitory casting proved successful in decreasing the positive support reaction. When casting was discontinued, the positive reaction returned. To provide a long-term solution for this problem, a polypropylene tone-inhibiting AFO was fabricated. It incorporated the same principles as the casts. The success achieved with casting was rapidly regained and then surpassed with the use of the tone-inhibiting AFO. Natural recovery might be cited by some as the cause for improvement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…67 ± 6 9 In addition to applying tension to increase the extensibility of a shortened muscle, some authors have suggested that serial casting may have an inhibitory eOE ect on the casted limb, resulting in a reduction of muscle overactivity. 39,45,53,54,70 Gossman et al 71 have stated that the principal eOE ect of serial casting is to alter muscle length rather than to in¯uence neurological activity. However, this distinction may be inappropriate as there is some evidence to suggest that the two outcomes are inextricably connected.…”
Section: Proposed Rationales For the Eoe Ect Of Serial Castingmentioning
confidence: 99%
“…67 ± 6 9 In addition to applying tension to increase the extensibility of a shortened muscle, some authors have suggested that serial casting may have an inhibitory eOE ect on the casted limb, resulting in a reduction of muscle overactivity. 39,45,53,54,70 Gossman et al 71 have stated that the principal eOE ect of serial casting is to alter muscle length rather than to in¯uence neurological activity. However, this distinction may be inappropriate as there is some evidence to suggest that the two outcomes are inextricably connected.…”
Section: Proposed Rationales For the Eoe Ect Of Serial Castingmentioning
confidence: 99%
“…The casting period may be followed by a regime of splinting or casting for shorter periods during the day. [7,9]. Some authors have observed increases in ankle dorsiflexion secondary to inhibitive casting [11,[13][14][15] and gait improvements have also been noted.…”
Section: Introductionmentioning
confidence: 99%
“…Serial casting is used variably to inhibit the overactivity of the ankle plantarflexors [3][4][5][6][7][8][9][10][11][12][13][14][15] or to lengthen components of the musculo-tendinous unit [16][17][18][19][20][21][22][23][24]. Typically, inhibition is thought to be achieved by maintaining the foot and ankle in a neutral position for a period of over 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of TRAFO literature consists of subjective studies that infer a reduction in spasticity based on observed changes in biomechanic and functional variables. 7,12,[20][21][22][23][24] Other criticisms include the lack of objective documentation of change in measured variables, lack of control groups and the potential bias of unblinded assessors. 25 The overall aim of TRAFO research is to evaluate effectiveness in reducing spasticity; however, no study to date has used a measurement tool sufficient to quantify this.…”
Section: Introductionmentioning
confidence: 99%